Inferring transcriptomic dynamics implicated in odor fatty acid accumulation in adipose tissue of Hulun Buir sheep from birth to market - Yechan Zhao; Zhangyan Li; Huimin Ou; Zhiliang Tan; Jinzhen Jiao (BMC Genomics)
Abstract This study aimed to investigate the temporal accumulation of odor fatty acids (OFAs) in the dorsal subcutaneous adipose tissue, and uncover their dynamic regulatory metabolic pathways from the transcriptomic perspective in lambs from birth to market. Thirty-two Hulun Buir lambs were selected and randomly assigned to four different sampling stages following their growth trajectories: neonatal (day 1), weaning (day 75), mid-fattening (day 150), and late-fattening (day 180) stages. Results indicated that the contents of three OFAs increased progressively as lambs matured, with the most drastic change occurred at mid-fattening vs. weaning. The dynamic transcriptomic profiles exhibited two distinct phases, with differentially expressed genes (DEGs) before weaning were involved in immune homeostasis, whereas those after weaning were associated with nutrient metabolism. Furthermore, DEGs involved in lipid metabolism and branch-chain amino acid degradation pathways exhibited surge in expression at mid-fattening vs. weaning, with acetyl-CoA and branched-chain-CoA as intermediates, and driven by regulation of PPAR and AMPK signaling pathways. Overall, our findings provided novel insight into the critical time window and pivotal candidate genes of OFA synthesis in the adipose tissue, which will assist with the targeted development of nutritional strategies to inhibit OFA accumulation of lambs.